Tantangan Penggunaan Bahasa Inggris Maritim Pada Awak Kapal dan Implikasinya Terhadap Keselamatan Operasional di Laut - Listriyawati, Nyoman; Supangat, Supangat (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
This research aims is to analyze the challenges of using Maritime English by ship crews and its impact on safety at sea. Through a survey approach, data was obtained from a number of ship crews at ports, especially at Tanjung Perak Port, Surabaya. The results showed variations in the level of Maritime English competency among respondents, with a number of challenges faced, such as difficulties in daily communication, document translation, and interactions with port authorities. These challenges have serious implications for safety at sea, including increased risk of accidents, operational delays, and the inability to respond quickly and appropriately to emergency situations. These safety implications highlight the urgency to improve maritime English competency among ship crews through appropriate training and the development of effective communication strategies. By improving maritime English skills, it can be hoped that safety risks at sea can be significantly reduced. This research provides valuable insights for the shipping industry and authorities to improve communication practices and increase safety at sea.